Internalisasi Nilai-Nilai Akhlak Mulia Melalui Pembelajaran Pai di SMP IT Nurul Yaqin Berbasis Pesantren - Robi Hilmy Maulana; Darnanengsih; Abdul azis Khoiri (CV. Ulil Albab Corp, 2026)
This study is motivated by the need for education to cultivate students who are not only academically competent but also possess noble character. A pesantren-based school is considered strategically advantageous because it integrates formal instruction, religious habituation, teacher exemplarity, and a religious school culture in the students' daily lives. This article aims to describe Islamic Education (PAI) learning strategies in instilling noble moral values, explain the role of PAI teachers in modeling and habituating moral conduct, and identify pesantren-based supporting activities that strengthen the internalization of moral values at SMP IT Nurul Yaqin. The study is designed using a qualitative descriptive approach. Data are planned to be collected through observation, in-depth interviews, and documentation involving PAI teachers, the principal, pesantren caregivers, and students. Conceptually, the intemalization of moral values proceeds through the stages of value transformation, value transaction, and transintemalization. These processes are reinforced through exemplary conduct, habituation, advice, a religious environment, and continuous supervision and evaluation. This manuscript underscores that pesantren-based PAI learning has the potential to become an effective model of character education because it integrates cognitive, affective, and psychomotor domains.